Penerapan Metode SQ3R Untuk meningkatkan Kemampuan Membaca Intensif Siswa kelas IX MTs Nahdliyatul Islamiyah Blumbungan Pamekasan - Rahmawati Ardila; Linta Wafdan Hidayah (Universitas Islam Madura, 2018)
The ability of intensive reading class IX students at MTs Islamiyah Nahdliyatul Blumbungan is still relatively low due to the use of conventional methods when teaching and learning process of reading and lack of student interest in reading. To solve this problem , it requires methods that can improve the ability of students in the learning process. One of them is SQ3R method that can be used to determine how to learn a research, critical thinking, creative and how to motivate and review what has been learned. The purpose of this study was to improve the intensive reading skills of class IX MTs Nahdliyatul Islamiyah Blumbungan, Pamekasan after using the SQ3R method. The method used is classroom action research (PTK), which consists of 4 stage, namely planning, action, observation, and reflection. The instruments used were student response questionnaires, teacher and student activity observation sheets, and intensive reading ability test questions. The results of this study can be concluded that 27 students who achieve the creteria mininum, while students who do not achieve the creteria were 3 students. The percentage of achievement in classical is 90% ≥ 60% while for the increase in the ability of intensive reading students from cycle I to cycle II amount to 0.41 which is classified as moderate. Based on these results it can be concluded that the implementation of SQ3R method can improve the ability of intensive reading class IX students at MTs Islamiyah Nahdliyatul Blumbungan. Keywords: SQ3R Method, Intensive Reading Ability, Learning Activity Abstrak: Kemampuan membaca intensif siswa kelas IX di MTs Nahdliyatul Islamiyah Blumbungan, Pamekasan yang masih tergolong rendah yang disebabkan oleh penggunaan metode konvensional pada saat pembelajaran membaca serta kurangnya minat siswa dalam membaca. Untuk menghadapi kendala tersebut diperlukan metode yang bisa mengadaptasi kemampuan siswa dalam proses pembelajarannya. Salah satunya adalah metode SQ3R yang dapat digunakan untuk mengetahui bagaimana belajar meneliti, berfikir kritis, kreatif dan bagaimana memotivasi diri sendiri dan meninjau kembali apa yang telah dipelajari. Tujuan dalam penelitian ini adalah untuk meningkatkan kemampuan membaca intensif siswa kelas IX MTs Nahdliyatul Islamiyah Blumbungan, Pamekasan setelah menggunakan metode SQ3R. Metode yang digunakan adalah penelitian tindakan kelas (PTK)yang terdiri dari 4 Tahap, yaitu perencanaan, tindakan, observasi, dan refleksi. Instrumen yang digunakan adalah angket respon siswa, lembar observasi kegiatan guru dan siswa, serta soal tes kemampuan membaca intensif. Hasil dari penelitian ini dapat dipaparkan bahwa siswa yang tuntas belajar secara individu sebanyak 27 orang, sedangkan siswa yang tidak tuntas belajar secara individu sebanyak 3 orang. Prosentase ketercapaian secara klasikal sebesar 90% ≥ 60% sedangkan untuk peningkatan kemampuan membaca intensif siswa dari siklus I ke siklus II adalah sebesar 0.41 yang tergolong sedang. Berdasarkan hasil tersebut maka dapat disimpulkan bahwa penerapan metode SQ3R dapat meningkatkan kemampuan membaca intensif siswa kelas IX MTs Nahdliyatul Islamiyah Blumbungan.